Aspectos da biologia, estrutura populacional e parentesco intranidal em vespas do gênero Trypoxylon (Hymenoptera: Sphecidae) - Peruquetti, Rui Carlos (Universidade Federal de São Carlos, 2003)
Wasps of the genus Trypoxylon (Sphecidae) building their nests with mud and mass-provisioned them with paralyzed spiders. The males of the subgenus Trypargilum may act as guards during the period of nest construction and provisioning. This behavior is common to other Sphecidae, but unusual in Hymenoptera. Theoretically, such behavior makes sense, due to haplodiploid and its relatedness asymmetry, only if male guards be the fathers of the female brood. In this study was investigated the population structure of T. (Trypargilum) albitarse and T. (Trypargilum) rogenhoferi, both common species in Brazil. Nests were sampled in São Carlos and Luís Antônio, State of São Paulo cities. Pupae and adults were analyzed using horizontal starch gel electrophoresis. The populations of the two species showed structured, probably as consequence of philopatric behavior of the wasps. In the case of T. rogenhoferi, behind philopatry, differentiate fecundity among females may be important to determine the observed population structure. Larger females produce more offspring than small ones and, on average, the daughters of these larger females are larger too. Thus, the larger females genotype may be the predominant in the nesting area. In this manner, T. rogenhoferi fits the predictions of the models on optimal sex allocation, another line of investigation in this study. Maternal provisions determined the size of each offspring and females allocated well-stocked brood cells to daughter, the sex that benefits most being large. This strategy yielded differences in size between the sexes, being the females larger than males. There are evidences local prey availability may influence the female decision of lay a male or a female egg and also influence the body size of both sexes, but furthers studies are necessary to test whether local resources enhancement might play some role in T. rogenhoferi populations. The guard paternity also was investigated and was verified to both species that in many cases the guard was the father of the female offspring, but the results are contradictory. The relatedness estimates (determined using variable enzyme systems as markers) have large standard errors; so many of the values do not differ from zero or 0.75 (full sisters). It was not possible to determine whether such deviations are due (i) multiple mating by females, (ii) nest switching and/or (iii) more than one female laying eggs in a nest. It was observed that (ii) and (iii) can occur in variable frequencies, being dependents of population density and availability of places to nesting. The occurrence of (i) may be possible whether the repeated copulations solicited by the guard from the female were not effective to assure to him the paternity. In areas with dense populations, extrapair copulations are frequent. Maybe, the adoption of another approach to determine the paternity in these wasps be the better solution to this question.
Keywords: Apoidea; Parentesco genético; Razão sexual; Alocação sexual; CIENCIAS BIOLOGICAS::GENETICA